Pemodelan Matematika Penyebaran Penyakit Toksoplasmosis dengan Pengaruh Vektor - Risman, Junero; Rosha, Media (UNIVERSITAS NEGERI PADANG, 2022)
Toxoplasmosis is a sickness as a result of the parasite Toxoplasma gondii, which can attack humans and animals, especially cats. The reason for this investigation is to discover the model, the results of model analysis, and an interpretation of the results of a mathematical model analysis of the spread toxoplasmosis by vector effects. The strategies used on this take a look at are descriptive. A mathematical model of the spread toxoplasmosis by vector influence takes the form of a nonlinear system of equations consisting of eight nonlinear equations. Analysis results of a mathematical model with two fixed points, a disease-free fixed point and a diseased fixed point. Each is asymptotically stable, subject to several conditions. The resulting baseline reproductive numbers indicate that the disease is becoming epidemic as the horizontal transmission rate and transmission rate from the latent population to the infected population within the vector increase.